Effect of semiquantitative culture results from complex host surgical wounds on dehiscence rates. Issue 2 (13th March 2017) - Elmarsafi, Tammer; Garwood, Caitlin S.; Steinberg, John S.; Evans, Karen K.; Attinger, Christopher E.; Kim, Paul J.
Abstract: The primary aim of this study was to determine the effect of positive bacterial cultures at the time of closure on dehiscence rates. Pre‐ and post‐débridement wound cultures from patients undergoing serial surgical débridement of infected wounds were compared with outcomes 30 days postoperatively. One‐hundred patients were enrolled; 35 were excluded for incomplete culture data. Sixty‐five patients were evaluated for species counts, including Coagulase negative Staphylococcus (CoNS), and semiquantitative culture data for each débridement. The post‐débridement cultures on the date of closure had no growth in 42 patients (64.6%) of which 6 dehisced (14.3%), and 36 remained closed; with no statistically significant difference in dehiscence rates ( p  = 0.0664). Pre‐débridement cultures from the 1st débridement of the 65 patients showed 8 patients had no growth, 29 grew 1 species, 19 grew 2 species, and 9 had 3–5 species. There was a reduction in the number of species and improvement of semiquantitative cultures with each subsequent débridement. The dehiscence rate for those who had 2 débridements ( n  = 42) was 21.4% at 30 day follow‐up and 21.7% in those who had 3 débridements ( n  = 23). The number of débridements had no statistical significance on dehiscence rates. The presence of CoNS on the day of closure was a statistically significant risk for dehiscence within 30 days ( p  = 0.0091) postoperatively. This data demonstrates: (1) positive post‐débridement cultures (scant/rare, growth in enrichment broth) at the time of closure did not affect overall dehiscence rates ( p  = 0.0664), (2) the number of species and semiquantitative culture results both improved with each subsequent débridement, (3) the number of surgical débridement did not influence postclosure dehiscence rates. (4) Positive cultures containing CoNS at the time of closure is a risk factor for dehiscence ( p  = 0.0091).